2014
DOI: 10.1148/radiol.13122654
|View full text |Cite
|
Sign up to set email alerts
|

Increased Unenhanced Bowel-Wall Attenuation at Multidetector CT Is Highly Specific of Ischemia Complicating Small-Bowel Obstruction

Abstract: Increased bowel-wall attenuation on unenhanced 64-section multidetector CT images is a specific sign for ischemia complicating SBO. Diagnostic accuracy of 64-section multidetector CT for ischemia associated with SBO was excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 29 publications
3
66
0
1
Order By: Relevance
“…Areas of decreased or absent bowel wall contrast enhancement, which is classically indicative of ischemic bowel wall in abdominal emergencies [24], were significantly associated with surgical BBMI (OR 4.4, 95 % CI 1.2-17). However, there were 11 false positives (33.3 %) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Areas of decreased or absent bowel wall contrast enhancement, which is classically indicative of ischemic bowel wall in abdominal emergencies [24], were significantly associated with surgical BBMI (OR 4.4, 95 % CI 1.2-17). However, there were 11 false positives (33.3 %) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Performing both unenhanced and contrast-enhanced CT improves test sensitivity, diagnostic confidence, and interobserver agreement in the diagnosis of ischemia. Decreased or absent mural enhancement after administration of IV contrast is a useful, highly specific, indicator of intestinal ischemia (95-100%), despite variable sensitivity of 40-60% [46,57,58]. A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60].…”
Section: Abdominal Ctmentioning
confidence: 99%
“…A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60]. This sign was 100% specific and 56% sensitive for bowel ischemia [57][58][59][60]. Other CT signs of ischemia include bowel wall thickening and mucosal thumbprinting from intramural edema, inflammation, or hemorrhage; pneumatosis intestinalis from intramural gas produced by bacteria; and streaky mesentery from adjacent inflammatory infiltration as listed in Table 2 [11•, 24].…”
Section: Abdominal Ctmentioning
confidence: 99%
“…Although multidetector contrast material-enhanced CT (with CT angiography) has shown high sensitivity in the diagnosis of acute bowel ischemia, several of the most common signs are nonspecific, including bowel wall thickening, bowel dilatation, mesenteric stranding, and mesenteric fluid. However, bowel wall hypoenhancement, the CT sign with the highest specificity (93%-100%), may go unrecognized (3)(4)(5)(6)(7)(8). Recognition of bowel wall hypoenhancement may be especially valuable early in acute presentation, when late secondary signs of infarction (both clinical and radiographic) have not yet developed.…”
Section: Implication For Patient Carementioning
confidence: 99%